2000
DOI: 10.1183/09031936.00.16590900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate alcohol upon obstructive sleep apnoea

Abstract: Moderate-to-large quantities of alcohol are known to aggravate severe obstructive sleep apnoea (OSA), however, the reported effects of moderate alcohol consumption upon mild-to-moderate OSA are inconsistent. Given the reported benefits of moderate alcohol consumption on cardiovascular mortality, recommendations regarding the management of patients with OSA are difficult to formulate. The aim of this study was to evaluate the effects of moderate alcohol on sleep and breathing in subjects with mild-to-moderate O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 26 publications
1
76
0
6
Order By: Relevance
“…This concurs with findings of BERRY et al [18], who reported that 0.5 g alcohol?kg -1 did not notably change breathing patterns during sleep. In contrast, moderate doses of alcohol (0.5-1 g?kg -1 ) increased the AHI without influencing apnoea length or oxygen desaturation [19]. Time spent in a supine position did not significantly affect the ODI variability factor.…”
Section: Variability Studymentioning
confidence: 81%
“…This concurs with findings of BERRY et al [18], who reported that 0.5 g alcohol?kg -1 did not notably change breathing patterns during sleep. In contrast, moderate doses of alcohol (0.5-1 g?kg -1 ) increased the AHI without influencing apnoea length or oxygen desaturation [19]. Time spent in a supine position did not significantly affect the ODI variability factor.…”
Section: Variability Studymentioning
confidence: 81%
“…These authors also highlighted that alcohol has a synergistic relationship with sleep deprivation, which increases chances of road accidents and reduces the academic performance of university students (7,8) . Studies carried out on adults in turn highlighted a statistically significant association between alcohol use and the development of sleep apnoea, poor sleep quality and sleep problems ( 9,(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…It also affects lung function and causes inflammation of the airways, generating a predisposition to snoring and apnoea. Smoking is still associated with disturbances in the structure of sleep, such as an increase in latency, excessive drowsiness during the day and a reduction in sleep (8)(9)(10) efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a significant association between OSAS and measures of excess body weight [1,11,13,[30][31][32][33][34][35][36][37][38][39]. Many studies in which defined quantities of alcohol were administered to healthy subjects or patients with OSAS before bedtime have demonstrated harmful effects on nocturnal respiration including increased number and duration of hypopnea and apnea events [40][41][42][43][44][45]. Many cross-sectional epidemiological studies of OSAS have found positive associations with cigarette smoking [4,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%